ทรานซิสเตอร์อิเล็กตรอนเดี่ยวและการประยุกต์ Single-Electron Transistors and Applications - สัมพันธ์อภัย สุธีร์; ฤทธิ์เจริญวัตถุ ศุภชัย (Science Essence Journal, 2014)
ปัจจุบันเทคโนโลยีสามารถสร้างอุปกรณ์อิเล็กทรอนิกส์ในระดับนาโนเมตร ทำให้พฤติกรรมของอุปกรณ์แตกต่างจากอุปกรณ์แบบดั้งเดิม ในอุปกรณ์ที่มีส่วนประกอบที่เรียกว่า “เกาะ” จะเชื่อมโยงกับภายนอกผ่านรอยต่อการทะลุผ่าน ลักษณะดังกล่าวทำให้เกิดความไม่ต่อเนื่องของระดับพลังงานอิเล็กตรอนภายในเกาะ ซึ่งนำไปสู่ปรากฏการณ์การขัดขวางแบบคูลอมบ์ ปรากฏการณ์นี้สามารถใช้ควบคุมอิเล็กตรอนเดี่ยวในอุปกรณ์ต่างๆ เช่น กล่องอิเล็กตรอนเดี่ยว และทรานซิสเตอร์อิเล็กตรอนเดี่ยว เพื่อให้เกิดปรากฏการณ์การขัดขวางแบบคูลอมบ์ โครงสร้างต้องประกอบด้วย รอยต่อการทะลุผ่าน รอยต่อตัวเก็บประจุ เกาะและขั้วไฟฟ้าที่เชื่อมโยงจากภายนอก โดยขั้วเกตทำหน้าที่ควบคุมระดับพลังงานของอิเล็กตรอนภายในเกาะ อิเล็กตรอนเดี่ยวจะทะลุผ่านรอยต่อการทะลุผ่านเข้า/ออกจากเกาะตามแรงดันไฟฟ้าที่ขั้วเกต แม้กล่องอิเล็กตรอนเดี่ยวเป็นอุปกรณ์ที่มีโครงสร้างพื้นฐานที่สุด แต่โครงสร้างนี้ไม่สามารถนำไปประยุกต์ใช้งานได้ ในขณะที่โครงสร้างอย่างง่ายของทรานซิสเตอร์อิเล็กตรอนเดี่ยวมีช่องทางให้อิเล็กตรอนผ่านได้ ทำให้โครงสร้างนี้สามารถใช้งานได้จริง ดังนั้น บทความนี้จะเน้นกลไกการทำงานและการประยุกต์ที่สำคัญของทรานซิสเตอร์อิเล็กตรอนเดี่ยว โดยอุปกรณ์ชนิดนี้ใช้พลังงานต่ำและมีความไวสูงต่อสนามไฟฟ้า ฉะนั้น ทรานซิสเตอร์อิเล็กตรอนเดี่ยวจึงสามารถประยุกต์ใช้งานในด้านต่างๆ ได้ เช่น ซุปเปอร์เซนซิทีฟอิเล็กทรอมิเตอร์ และเกตตรรกะอิเล็กตรอนเดี่ยว อย่างไรก็ตาม อุปกรณ์นี้ยังต้องได้รับการวิจัยและพัฒนาเพิ่มเติมเพื่อให้สามารถผลิตในเชิงพาณิชย์ได้ The state-of-the-art technology can be used to fabricate nanoscale electronic devices. The nanoscale electronic device does not show the same behavior as a traditional electronic device, but exhibits the quantum phenomena. In the nanostructure, an isolated part, so-called çislandé, is connected to an external electrode via a tunneling junction. With this nanostructure and connection, the discreteness of electron states leads to the coulomb blockade phenomenon. This quantum phenomenon can be used to control a single electron in various single-electron devices, such as single-electron boxes and single-electron transistors. To produce the coulomb blockade effect, the structure of single-electron devices must be consisted of tunneling junctions, capacitive junctions, islands and electrodes which are connected to external leads. The voltage is applied to the gate electrode to control the increase or decrease of a single electron in the island. A single-electron box has the simplest structure among these devices. However, the structure of single-electron boxes is impractical for utilization. In contrary to the box, the simple structure of single-electron transistors does not trap the electron inside their island. With its passable structure, the transistor can be used in practice. This article therefore focuses on the mechanism of single-electron transistors, as well as their main applications. The single-electron transistor not only consumes low energy, but also has high sensitivity to the electric field. They are thus used in various applications, such as supersensitive electrometers and single-electron logic gates. However, some further research and development are needed to commercialize these single-electron devices.